Androgen receptor profiling predicts prostate cancer outcome. Issue 11 (27th September 2015) - Stelloo, Suzan; Nevedomskaya, Ekaterina; van der Poel, Henk G; de Jong, Jeroen; van Leenders, Geert JLH; Jenster, Guido; Wessels, Lodewyk FA; Bergman, Andries M; Zwart, Wilbert
Abstract: Prostate cancer is the second most prevalent malignancy in men. Biomarkers for outcome prediction are urgently needed, so that high‐risk patients could be monitored more closely postoperatively. To identify prognostic markers and to determine causal players in prostate cancer progression, we assessed changes in chromatin state during tumor development and progression. Based on this, we assessed genomewide androgen receptor/chromatin binding and identified a distinct androgen receptor/chromatin binding profile between primary prostate cancers and tumors with an acquired resistance to therapy. These differential androgen receptor/chromatin interactions dictated expression of a distinct gene signature with strong prognostic potential. Further refinement of the signature provided us with a concise list of nine genes that hallmark prostate cancer outcome in multiple independent validation series. In this report, we identified a novel gene expression signature for prostate cancer outcome through generation of multilevel genomic data on chromatin accessibility and transcriptional regulation and integration with publically available transcriptomic and clinical datastreams. By combining existing technologies, we propose a novel pipeline for biomarker discovery that is easily implementable in other fields of oncology. Synopsis: Investigation of chromatin accessibility in prostate specimens identified potential driving transcription factors in prostate tumorigenesis, including androgen receptor (AR). AR ChIP‐seq unveiled distinct profiles that bear prognostic potential and can stratify patients on outcome. Chromatin is more condensed in healthy prostate as opposed to prostate tumors. Motif sequences for AR and its interactors are enriched at accessible chromatin sites. AR chromatin binding sites differ between primary and progressive prostate cancer. Genes with a proximal differentially bound AR chromatin site can stratify patients with prostate cancer on outcome. The gene classifier can be used alone or in combination with the D'Amico classification to improve risk stratification for biochemical recurrence. Abstract : Investigation of chromatin accessibility in prostate specimens identified potential driving transcription factors in prostate tumorigenesis, including androgen receptor (AR). AR ChIP‐seq unveiled distinct profiles that bear prognostic potential and can stratify patients on outcome.